(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Bullous emphysema affects more than 5% of the world’s population, with almost 12% among adults over 30 years of age. It also ranks as the third leading cause of death in the US and kills over 120,000 people a year. It is also known that this disease causes spontaneous pneumothorax in 70-80% of cases. Currently, there is no consensus on the etiology, pathogenesis, clinic, diagnosis and treatment of bullous lung disease. According to the literature, surgical reduction of lung volume in the development of complications of bullous disease shows a high percentage of good immediate and long-term results by improving the physical capabilities of patients, eliminating shortness of breath, improving the quality of life and survival. Nevertheless, the search for effective minimally invasive methods of surgical treatment of patients with bullous pulmonary emphysema continues.